INVENTORY MANAGEMENT AND SUSTAINABLE PERFORMANCE OF STATE CORPORATIONS IN KENYA - Gatari , Catherine; Shale, Noor; Osoro, Anthony (International Journal of Supply Chain Management, 2022)
Purpose: The purpose of this study was to examine the effect of inventory management on sustainable performance of state corporations in Kenya. Methodology: The descriptive research design was applied in carrying out the study. The respondents of the study included the heads of finance and procurement department in all 187 state corporations in Kenya. Census was used in this study where the head of procurement department and the head of finance in each state corporation that resulted to 374 study respondents. This study used a questionnaire as the main research tool to collect primary data. Descriptive analysis and inferential analysis was carried out which was made possible through the use of Statistical Package for Social Sciences (SPSS) version 26. Findings: Inventory management significantly affected the sustainability of state corporations in Kenya at p<0.05. This shows that upholding inventory management would be essential in steering the sustainable performance of the state corporations. The regression model established that the R value was 0.633 while the R2 was 0.401 which indicated that the variability of the inventory management on the sustainable performance of the state corporations in Kenya could be explained by up to 40.1% of the model and the P-value was 0.000<0.05. This implies that the model was fit to determine the relationship between the inventory management and sustainable performance and therein make conclusions and recommendations. Unique contribution to theory, practice and policy: While the existing inventory management theory used in this study was validated, the study recommends that the accounting as well as procurement officer in each state procuring entity need to ensure that all proper stock levels are kept as per the regulation through proper verification and processing of all requirements, adhering to prescribed stock policies in the Regulation and ensuring that they duly consider safety stock and lead time when replenishing to ensure appropriate stock levels are kept at all time. The study recommended that public procuring entities policy makers need to establish a policy framework to expedite effective adoption of best inventory management systems to facilitate sustainable performance.